Guidelines for using animal models in blast injury research. Issue 1 (23rd February 2019) - Watts, Sarah; Kirkman, E; Bieler, D; Bjarnason, S; Franke, A; Gupta, R; Leggieri Jr, M J; Orru, H; Ouellet, S; Philippens, M; Sarron, J-C; Skriudalen, S; et al.
Abstract : Blast injury is a very complex phenomenon and frequently results in multiple injuries. One method to investigate the consequences of blast injuries is with the use of living systems (animal models). The use of animals allows the examination and evaluation of injury mechanisms in a more controlled manner, allowing variables such as primary or secondary blast injury for example, to be isolated and manipulated as required. To ensure a degree of standardisation across the blast research community a set of guidelines which helps researchers navigate challenges of modelling blast injuries in animals is required. This paper describes the guidelines for Using Animal Models in Blast Injury Research developed by the NATO Health Factors and Medicine (HFM) Research Task Group 234.